2018
DOI: 10.22616/reep.2018.015
|View full text |Cite
|
Sign up to set email alerts
|

Research of the Relationship of Criminal Violence, Adult Attachment Styles and Personality Traits of Violent Male Offenders

Abstract: The problem of assessing criminal attitudes towards violence of violent offenders is very essential. It is important to measure criminal attitude using valid procedures as Self-Concept Implicit Association Test (IAT) and also consider its relationship with additional variables as attachment styles and personality traits, that could help to explain the forming and maintaining criminal attitude towards violence. The aim of this study is to research the relationship of criminal violence, adult attachment styles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Research suggests a link between insecure attachment and (sexual) violent behavior (Miller & Klockner, 2019; Yang & Perkins, 2021). For example, Simane-Vigante et al (2018) reported that anxious-ambivalent attachment styles are common in a sample of 77 males with violent convictions. Also, Garofalo & Bogaerts (2019) showed that avoidant and anxious attachment dimensions were dominant in a sample of 84 perpetrators of child sexual abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests a link between insecure attachment and (sexual) violent behavior (Miller & Klockner, 2019; Yang & Perkins, 2021). For example, Simane-Vigante et al (2018) reported that anxious-ambivalent attachment styles are common in a sample of 77 males with violent convictions. Also, Garofalo & Bogaerts (2019) showed that avoidant and anxious attachment dimensions were dominant in a sample of 84 perpetrators of child sexual abuse.…”
Section: Discussionmentioning
confidence: 99%
“…They are thus more liable to become angry and react violently. In contrast, introverts can control their actions, especially in violent circumstances ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…& Plotka (2018). Estas personas, a muy temprana edad, asimilan el contener, desear o querer llevar a cabo un acto delictivo y, por tal razón, una vez que un delincuente tenga de forma organizada su personalidad, emitirá de manera repetitiva e impulsivamente estas conductas delictivas(Rawlings et al, 2021).Para Eysenck, las propuestas desde las dimensiones de la personalidad se caracterizan por ser descritas desde los factores disposicionales, que se asocian a los comportamientos ajustados por la sociedad, como lo describeLebuda et al, (2021).…”
unclassified